Genetic Association of CHAT rs3810950 and rs2177369 Polymorphisms with the Risk of Alzheimer's Disease: A Meta-Analysis. (15th August 2016) - Liu, Yong; Chen, Qicong; Liu, Xu; Dou, Mengmeng; Li, Silu; Zhou, Jiahui; Liu, Hong; Wu, Yongfu; Huang, Zunnan
Abstract : Choline acetyltransferase (CHAT) rs3810950 and rs2177369 polymorphisms have been implicated in susceptibility to Alzheimer's disease (AD). Due to the inconsistent results from previous studies, a meta-analysis was performed to estimate the association between these polymorphisms and AD risk more precisely. Pooled results of our meta-analysis indicated CHAT rs2177369 polymorphism was correlated with decreasing AD risk in one of five genetic models (dominant: OR = 0.77, 95% CI: 0.62–0.96), while rs3810950 mutant was associated with AD development in three models (allelic: OR = 1.18, 95% CI: 1.01–1.37, homozygous: OR = 1.63, 95% CI: 1.09–2.42, and recessive: OR = 1.65, 95% CI: 1.20–2.26). In subgroup analysis by ethnicity, the association between CHAT rs3810950 polymorphism and AD risk was just found in the recessive model (OR = 1.47, 95% CI: 1.05–2.07) among Caucasians, while four genetic models (allelic: OR = 1.23, 95% CI: 1.01–1.48; homozygous: OR = 2.24, 95% CI: 1.48–3.39; dominant: OR = 1.21, 95% CI: 1.06–1.40; and recessive: OR = 2.18, 95% CI: 1.45–3.29) assumed this association in Asians. In conclusion, our meta-analysis indicated CHAT rs2177369 polymorphism might play a protective role in AD, while rs3810950 variant was a risk factor for AD but its single heterozygous mutations might not influence susceptibility to AD.